Assistance in identifying potential occupational safety and health hazards for woven bamboo craftsmen in Tasikmalaya - Isyeu Sriagustini; Teni Supriyani (Community Development Journal, 2021)
The informal sector business supports the economy in Indonesia. However, It has various potential hazards. Occupational safety and health (OSH) must be implemented in all workplaces, both formal and informal. OSH efforts focus more on disease prevention and health promotion to change workers' behavior meeting occupational health standards. One of them is increasing workers' knowledge. This community service aims to disseminate the study results of the potential hazards of the work environment in each process of making bamboo weaving crafts. The method used community empowering  There were 20 participants consisting of bamboo SMEs owners and the craftsmen who joined the bamboo SMEs association. The results showed that most participants never knew that there were potential hazards in every stage of making woven bamboo crafts before  the accompaniment.  However, they became more understanding of the potential hazards in their workplace after accompaniment. In conclusion, craftsman's understanding levels of the potential hazards in the work environment increased after accompaniment. potential hazards in the process of making bamboo crafts. SMEs owners and artisans should consider potential risks in the workplace to form safe behavior at work.